COMMD3 Expression Affects Angiogenesis through the HIF1α/VEGF/NF-κB Signaling Pathway in Hepatocellular Carcinoma In Vitro and In Vivo. (2nd September 2022) - Zhu, Tingting; Peng, Xiaolin; Cheng, Ziwei; Gong, Xiuru; Xing, Dongwei; Cheng, Wei; Zhang, Minguang
Abstract : Background . High expression of copper metabolizing MURR1 domain (COMMD3) is significantly correlated with poor prognosis in hepatocellular carcinoma (HCC) patients. Here, we explored the mechanism by which COMMD3 affects HCC angiogenesis through the HIF1 α /VEGF/NF- κ B signaling pathway. Methods . SK-Hep1 and Hep-3B cell lines were transfected by COMMD3 overexpression and RNA interference lentivirus and verified using RT-qPCR and western blotting techniques. Using RNA sequencing, we analyzed differentially expressed genes in COMMD3 -overexpressed and COMMD3 -knockdown HCC cells. Altogether, colony formation assay, wound healing assay, transwell cell invasion assay, flow cytometry apoptosis experiments, HUVEC tube formation detection, phalloidin staining assay, western blotting, immunohistochemical staining, and a nude mouse xenograft model were used for experimental verification. Results . Lentivirus COMMD3 overexpression and knockdown were successfully established in HCC cells. COMMD3 overexpression significantly promoted the proliferation, angiogenesis, migration, and invasion capacities of HCC cells with no obvious effect on apoptosis versus controls while COMMD3 knockdown showed the opposite trend. The expression and protein levels of COMMD3 as well as HIF1 α, VEGF, and NF- κ B were increased in COMMD3 -overexpressing HCC cells versus control cells, while they were reduced after COMMD3 knockdown. In addition, RNA-seq indicated that COMMD3 is an indispensable gene for HCC angiogenesis through HIF1 α and NF- κ B signaling pathways. Conclusion . This study showed that low expression of COMMD3 can inhibit HCC angiogenesis by suppressing the HIF1 α /VEGF/NF- κ B pathway. This implicates COMMD3 as a potential biomarker for improving the therapeutic outcome of HCC.